Análisis comparativo entre paradigmas de programación y su influencia en un proyecto de desarrollo de software - Márquez Mora, Heidy Beatriz (2022)
This case study addresses the theme "comparative analysis between programming paradigms and their influence on a software development project" whose main objective is to determine the relationship between programming paradigms and the influence on the development of a project. of software since during the study within the technical university of Babahoyo a lack of knowledge about the different programming paradigms was identified by the students of the systems engineering career and this generates inconveniences when creating software programs. In order to have a better approach to the topic addressed, a survey was carried out on the students of the aforementioned career and the present case study was developed through the qualitative method and descriptive research, which help in the identification and definition of the variables put into study. in order to generate specific conclusions and recommendations that allow a solution to the problem raised.